STUDY OF TRADITIONAL SHRIMP FARMING; A CASE STUDY OF POND PRODUCTIVITY OF SEVERAL REGIONS IN INDONESIA - Handayani Boa; Sasitorn Suwannathep; Bambang Indratno Gunawan; Boosya Bunnag (LPPM Sekolah Tinggi Teknologi Cipasung, 2023)
Traditional shrimp farming in Indonesia is still dominant aquaculture and the one of large contributions in fisheries sector, namely provinces from Kalimantan, Java, West Nusa Tenggara (NTB), Sumatera, and Sulawesi. Pond farmers still maintain the old ways of managing their shrimp farming however some regions is found to apply sustainable shrimp farming with eco-friendly farm. In order to achieve sustainable income, the pond productivity is mainly calculated however pond productivities of those regions are not always correlated to the wider pond area and larger production. The objective of study is to explore traditional pond performance and its productivities in several provinces in Indonesia. The result shows that the shrimp farming are applying traditional method in pond management, water and soil quality is influenced by around the environment, the wide pond size/extensive pond, the opened pond, irregular pond shape, without feeds, built in the coastal areas and deltas as the brackish water pond, and harvest period after 4-6 months of cultivation. Seven provinces (South Sulawesi, West Java, East Java, Center Java, NTB, Southeast Sulawesi, and East Kalimantan provinces) in Indonesia contribute approximately 91% of total traditional shrimp farming production in Indonesia. Province with the second largest pond area in Indonesia is South Sulawesi province after North Kalimantan, however West Java is the biggest income of them compared, approximately IDR13.5 trillion. Government policy should facilitate improving environmental quality and sustainability in ponds in those regions.